Handgrip strength as a predictor of physical fitness in children and adolescents - Victor Keihan Rodrigues Matsudo; Sandra Mahecha Matsudo; Leandro Fornias Machado de Rezende; Vagner Raso (Universidade Federal de Santa Catarina, 2014)
The objective of this study was to examine the association between hangrip strength and physical fitness in children and adolescents at different stages of sexual maturation. We measured body composition and handgrip strength in 233 children and adolescents (10 - 17 years-old), who varied in terms of pubertal status. The subjects also performed the vertical jump test, standing long jump and sit-ups, as well as tests of flexibility, agility and speed. The level of energy expenditure was assessed with the international physical activity questionnaire. Handgrip strength differed by pubertal status, regardless of gender, whereas other parameters of physical fitness differed by gender and in the sample as a whole. Handgrip strength was consistently and independently associated with all other physical fitness variables, regardless of gender; some of those were mediated by energy expenditure (i.e., speed in seconds and in meters per second for the sample as a whole). The strength of the association between handgrip strength and physical fitness ranged from 20% (vertical jump test: R2=.20; P=.001) to 47% (speed in meters per second: R2=.47; P=.001). Our results support the idea that handgrip strength is consistently associated with several distinct parameters of physical fitness, regardless of age, gender or sexual maturation, suggesting that handgrip strength could be a highly accurate, independent predictor of physical fitness.